2019
DOI: 10.18521/ktd.492274
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Acute Pancreatitis Severity of Platelet Lymphocyte Ratio, Neutrophil Lymphocyte Ratio, Erythrocyte Distribution Width and Mean Platelet Volume

Abstract: Bu çalışmada sistemik inflamasyon ile ilişkili bir marker olduğu gösterilen; Nötrofillenfosit oranı (NLR), platelet-lenfosit oranı (PLR), ortalama trombosit hacmi (MPV) ve Eritrosit dağılım hacmi (RDW) ile akut pankreatitin (AP) başvuru anındaki ciddiyetini gösteren Ranson kriteri ile aralarındaki ilişkinin gösterilmesi amaçlanmıştır. Gereç ve Yöntem: Ocak 2017 ile Kasım 2018 tarihleri arasında AP tanısı ile takip eden hastaların verilerine retrospektif olarak ulaşıldı. 82 biliyer ve 15 nonbiliyer olmak üzere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Although mean platelet volume (MPV), which is another parameter in the CBC, is generally used to evaluate platelet functions in routine practice, it has been reported to show inflammatory load and disease activity. Also, MPV has been reported to be associated with disease activity in unstable angina, ulcerative colitis, myocardial infarction, pre-eclampsia, and Crohn's disease (11). In our study, we detected that neutrophil, MPV, and NLR values were significantly higher in patients diagnosed with the acute coronary syndrome in the emergency department (inpatients) than patients who were not diagnosed with ACS (outpatients).…”
Section: Discussionsupporting
confidence: 46%
“…Although mean platelet volume (MPV), which is another parameter in the CBC, is generally used to evaluate platelet functions in routine practice, it has been reported to show inflammatory load and disease activity. Also, MPV has been reported to be associated with disease activity in unstable angina, ulcerative colitis, myocardial infarction, pre-eclampsia, and Crohn's disease (11). In our study, we detected that neutrophil, MPV, and NLR values were significantly higher in patients diagnosed with the acute coronary syndrome in the emergency department (inpatients) than patients who were not diagnosed with ACS (outpatients).…”
Section: Discussionsupporting
confidence: 46%
“…The results of the regression analysis performed to determine the risk factors for prolonged hospitalization. In recent years, many articles aiming to show the relationship between hematological inflammation parameters and the severity of acute pancreatitis have been published [7,8]. Kaya et al in a study conducted by 418 acute pancreatitis patients admitted to the emergency department were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Han et al in a study conducted by; A positive correlation was found between the neutrophil lymphocyte ratio (NLR), another inflammation parameter, and Ranson criteria [9and theirs utility for predicting severity of AP was evaluated by receiver operator characteristic (ROC]. In a study by Önmez et al, NLR was shown to be an independent risk factor in showing the severity of acute pancreatitis [8].…”
Section: Discussionmentioning
confidence: 99%
“…RDW has been investigated in several diseases, such as rheumatoid arthritis, psoriasis, heart failure, and cutaneous vasculitis, and has been considered as a marker of inflammation [25]. The MCV/RDW ratio is used to evaluate for many diseases such as acute pancreatitis, cardiovascular disease [26,27].…”
Section: Discussionmentioning
confidence: 99%